2020
DOI: 10.1002/jbm.a.36905
|View full text |Cite
|
Sign up to set email alerts
|

Repair of facial nerve crush injury in rabbits using collagen plus basic fibroblast growth factor

Abstract: Facial nerves are frequently crushed or cut during facial surgery. In this study, the feasibility of repairing facial nerves in rabbits after crush or cut off injury was evaluated using collagen conduits with A collagen‐binding domain (CBD)‐human basic fibroblast growth factor (bFGF). A total of 39 six‐month‐old New Zealand White rabbits were randomly divided into four groups of nine rabbits, and bilateral crush or cut off injuries were made on each animal's face. Three rabbits were classified as the healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Besides, a collagen conduit was combined with bFGF to repair facial nerve injury in rabbits. The results of the electrophysiological examination and histological examination showed that the collagen conduit with CBD-bFGF was helpful for nerve repair [ 82 ].…”
Section: Biomaterial-based Bfgf Delivery In the Different Nervous Sys...mentioning
confidence: 99%
“…Besides, a collagen conduit was combined with bFGF to repair facial nerve injury in rabbits. The results of the electrophysiological examination and histological examination showed that the collagen conduit with CBD-bFGF was helpful for nerve repair [ 82 ].…”
Section: Biomaterial-based Bfgf Delivery In the Different Nervous Sys...mentioning
confidence: 99%
“…Growth factors are involved in the regulation of various cellular processes. Combining collagen-based nerve conduits with growth factors could create a more appropriate microenvironment for nerve • Rat-tail collagen gel with the anchored bFGF (Ma et al, 2017) • Functional recovery and nerve growth similar to autograft (Ma et al, 2017) • Rat (Ma et al, 2017) Frontiers in Bioengineering and Biotechnology frontiersin.org • Promotes neurite extension (Fujimoto et al, 1997) • Linear ordered collagen scaffold (LOCS) filled with collagen binding bFGF (CBD-bFGF) (Ma et al 2014a, Cui et al 2014 • Sustained release (Ma et al 2014a, Cui et al 2014 • Sciatic nerve (Ma et al 2014a, Fujimaki et al, 2017 • Rat (Ma et al 2014a, Fujimaki et al, 2017 • Stimulates SCs proliferation (Wang et al, 2003) • Oriented collagen tubes (Fujimaki et al, 2017) • Guide axon growth, promote nerve regeneration and functional restoration (Ma et al 2014a, Cui et al 2014 • Facial nerve (Cui et al 2014, Wang et al 2020 • Minipigs (Cui et al 2014) • Collagen conduits filled with CBD-bFGF (Wang et al, 2020) • Improved nerve repair and recovery of motor function (Fujimaki et al, 2017) • Rabbit (Wang et al, 2020) • Combine with CNTF (Cui et al, 2014) • Promote functional facial nerve recovery (Wang et al, 2020) • Synergistic effect (Cui et al, 2014) Ciliary neurotrophic factor (CNTF)…”
Section: Growth Factorsmentioning
confidence: 99%
“…The N-terminal of native bFGF was fused with a CBD, TKKTLRT, which could specifically bind to collagen (Li et al, 2011;Ma et al, 2014a). The sustained release of the bFGF further improved nerve regeneration in vivo (Cui et al, 2014;Wang et al, 2020).…”
Section: Basic Fibroblast Growth Factormentioning
confidence: 99%
“…The use of conduits for neural repair is a common strategy where different materials and/or grafts are implanted at the injury site to guide the neuronal regeneration. 107 Different additives have been tested on the fabricated scaffolds for neuronal regeneration, such as fibroblast growth factor, 108 IL-6, neurotrophins, glial-derived neurotrophins, and persephin. 109 Most of the reported studies have used pluripotent stem cells because they are easy to harvest and readily differentiate to nerve tissue.…”
Section: Craniofacial Nerve Tissue Engineeringmentioning
confidence: 99%